2014
DOI: 10.1186/1475-2859-13-33
|View full text |Cite
|
Sign up to set email alerts
|

A novel platform for heterologous gene expression in Trichoderma reesei (Teleomorph Hypocrea jecorina)

Abstract: BackgroundThe industrially applied filamentous fungus Trichoderma reesei has received substantial interest due to its highly efficient synthesis apparatus of cellulytic enzymes. However, the production of heterologous enzymes in T. reesei still remains low mainly due to lack of tools for genetic engineering.ResultsIn this study we present new genetic tools for T. reesei to further expand its use in industrial production. We have developed an expression platform where genes are inserted into a versatile express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…1). To indicate that these two genes are part of the sorbicillin biosynthetic cluster, we will – in agreement with [26] - further name them sor1 (= pks11 ) and sor2 (= pks10 ) throughout the manuscript.
Fig. 1Phylogenetic analysis of SOR1/SorA ( T. reesei PKS11) and SOR2/SorB ( T. reesei PKS10) proteins by PhyML.
…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…1). To indicate that these two genes are part of the sorbicillin biosynthetic cluster, we will – in agreement with [26] - further name them sor1 (= pks11 ) and sor2 (= pks10 ) throughout the manuscript.
Fig. 1Phylogenetic analysis of SOR1/SorA ( T. reesei PKS11) and SOR2/SorB ( T. reesei PKS10) proteins by PhyML.
…”
Section: Resultsmentioning
confidence: 83%
“…Baker et al [24] have recently compared the polyketide synthase (PKS) inventory of three Trichoderma species ( T. reesei , T. virens and T. atroviride ) and showed that two polyketide synthase encoding genes - pks10 , pks11 - were unique to T. reesei. Pks10 and pks11 are located head-to-head in the center of chromosome 5 [25] and were shown to be responsible for the synthesis of sorbicillinoids [26]. These are complex cyclic polyketides, some of which have been shown to exhibit cytostatic and neuroprotective effects [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decisive advantage of this strain for its extensive application is the salient secretory capacity, not only for the three cellulolytic enzymes (cellobiohydrolase, endo-β-1,4-glucanase, β-glucosidase) [5], but also for various heterologous proteins [6]. Additionally, excellent post-translational modifications such as glycosylation and phosphorylation together with simplified downstream purification make these versatile model fungi more suitable for heterologous expression [7].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, low productivity of this fungus held back its further applications. Among the solutions, heterologous expression is always counted upon for its high efficiency and practicability [6]. There are various host candidates for removing this bottleneck [10], such as the prevalent prokaryotic Escherichia coli, eukaryotic yeast, and T. reesei.…”
Section: Introductionmentioning
confidence: 99%